Penerapan Model Pembelajaran Flipped Classroom Berbasis Video Animasi dalam Meningkatkan Minat Belajar Siswa di SMPN 1 SANROBONE - Resdi Resdi; Asy Syifah; Syarifah Hijrah Febrianti; Riza Sativani Hayati (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the implementation of video animation-based flipped classroom learning model in increasing students' learning interest in science subjects with material on the structure and function of living organisms in class 8D at SMPN 1 Sanrobone. The low interest in learning science among students is a major problem that needs to be addressed through more attractive and interactive learning innovations. The video animation-based flipped classroom model was chosen because it can optimize classroom learning time for more meaningful activities, while basic concept understanding is done independently through engaging animated videos. This study uses a survey method with a descriptive quantitative approach. The research subjects were students of class 8D SMPN 1 Sanrobone in the even semester of the 2024/2025 academic year. Research instruments used learning interest questionnaires, observations, and documentation. The results showed that the implementation of video animation-based flipped classroom model was able to increase students' learning interest with high categories in aspects of attention, interest, involvement, and learning satisfaction. Animated videos presented before face-to-face learning provide clear visualizations of the structure and function of living organisms, making students more prepared and enthusiastic to participate in discussions and practical activities in class. This learning model also encourages student learning independence and increases active interaction in learning. This study recommends the implementation of video animation-based flipped classroom as an alternative effective and innovative science learning strategy to increase students' learning interest.